Exploring Financial Behavior among Lecturers: The Mediating Role of Financial Self-Efficacy in Indonesia and Timor Leste - Mochamad Syafruddin Aji; Leonardo Bele Bau Amaral; Ayu Candra Kusuma; Tanza Dona Pertiwi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Main Purpose - This study examines lecturers’ financial behavior in Indonesia and Timor Leste by positioning financial self-efficacy as a mediating variable in the relationship between income, financial literacy, financial experience, and financial behavior. Method - This study employed a quantitative approach using primary data collected through a survey of 112 lecturers in Indonesia and Timor Leste. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Main Findings – The findings reveal that income, financial literacy, and financial experience do not directly determine lecturers’ financial behaviour. Instead, these factors significantly influence financial self-efficacy, which in turn has a significant positive effect on financial behaviour. The non significant direct effects and significant indirect effects indicate that financial self-efficacy fully mediates the relationship between income, financial literacy, financial experience, and financial behaviour. Thus, responsible financial behaviour is more strongly shaped by lecturers’ confidence in managing financial decisions than by economic capacity, knowledge, or experience alone. Theory and Practical Implications – This study highlights financial self-efficacy as a psychological mechanism linking economic, cognitive, and experiential factors to financial behaviour. Practically, universities should strengthen lecturers’ financial confidence through practice oriented programs. Novelty - This study contributes by examining financial self efficacy as a key mediator in a cross country lecturer context.